Online Advertising and Digital Marketing Law: How Influencers Can Impact the E-Commerce Market and its Legal Implications in Indonesia - Permata, Firly; Syarifah Nadia (Fakultas Hukum Universitas Airlangga, 2024)
In 2022, Indonesian influencers have been accused of false advertising in promoting binary option applications through social media platforms such as Instagram and TikTok. Influencers use various promotional methods to promote brands, one of which is uploading content through social media platforms to be marketed to their followers. However, online advertising and consumer protection are subject to various legal issues that influencers must navigate to ensure compliance with relevant laws and regulations. Influencers must ensure that their advertisements are honest and undisputed. Influencers must ensure that the uploaded content is truthful and not misleading, and must be able to support any claims made in their content. Failure to do so may result in legal action from consumer protection commissions or government agencies including law enforcement officials. In this paper, a legal understanding of the process of using influencers can introduce legal requirements for influencers to comply with related regulations, official guidelines, and influencer agreements. Such explicit and/ or implicit provisions to be fulfilled in the influencer agreement for example representations and warranties for the authenticity of the content created by influencers. In this paper, this study will use a systematic method to solve research problems through qualitative method and data collection using a statutory approach, a conceptual approach, interpretation of the data collected, and drawing conclusions about the research data. The data in this paper analyzes legal issues regarding influencer responsibilities in digital marketing and consumer protection laws, oversight from regulatory bodies and law enforcement officials in supervising social media endorsements, and mandatory clauses in influencer agreements. The study highlights that while influencer marketing drives substantial economic activity, it also poses various legal challenges that must be addressed to protect consumer rights and maintain market integrity. Key legal issues shall include the need for clear disclosure of sponsored content and protection against misleading advertisements.